ANALISIS SPASIAL PERUBAHAN TUTUPAN LAHAN PADA WILAYAH PERTAMBANGAN - Zulkarnain Zulkarnain; Halili Halili; Laode Diara (Universitas Haluoleo, 2015)
This study aims to determine in the mining area of PT Bumi Konawe Abadi District of Motui the period 2009 and 2015. Processing is done by using a computer that is equipped with ArcGIS software. Implementation of this study consists of several stages. that is pre-processing, digital image processing, classification OBIA, vicual interpretation, ground check and Land Cover Change Analysis. The results showed that in the period 2009 to 2015 there are 6 classes of land cover has decreased the extent of that class of forests, farms, mixed farms, secondary mangrove forests, water and shrubs. There are sour classes of land cover the increased area is mine, open land, fields, and settlements. The greatest extent of the decline occurred in forest cover has decreased by -171.22 ha area. The addition of the greatest extents occurred on land cover Mine is 167.44 ha. Key words : land cover and changes, Mining area, Forest.